Selected Excerpts from the Unrelenting History of the Human Race, Vol. 4 - Sy, Dominic (Likhaan: The Journal of Contemporary Philippine Literature, 2023)
“Selected Excerpts from the Unrelenting History of the Human Race, vol. 4” is a suite of flash fiction pieces that explores the complicated relationship between art, narration, and human/historical development. The stories take place across a wide range of times and spaces—from Manila to Constantinople, from our ancient past to our distant futures. in doing so, these stories seek to interrogate not only how we understand the creation of the world we live in but also the creation of worlds that we may still be able to make.